Analisis Efektivitas Kerja Pegawai Melalui Komunikasi dan Lingkungan Kerja - Ida Nirwana; Esi Sriyanti; Anisa Nurdyanti (Komunitas Dosen Indonesia, 2025)
Recognizing the significance of human resource management in attaining organizational objectives, firms and leaders must enhance their focus on communication and the workplace environment for their employees. This study seeks to examine the impact of communication and work environment on employee effectiveness at the Human Resources Development and Personnel Agency (BKPSDM) of Solok City. This research is a quantitative analysis. The utilized data are primary data acquired via questionnaires disseminated to respondents. The study population consisted of 41 employees from the Human Resources Development and Personnel Agency (BKPSDM) of Solok City. The sample method employed in this investigation was complete sampling. The study sample comprised 41 individuals. The employed data analysis methods included research instrument testing, multiple linear regression analysis, hypothesis testing, and coefficient of determination testing. The data test results indicate that the communication variable does not influence employee work effectiveness. The work environment influences employee productivity. Subsequently, communication and the work environment collectively influence employee productivity. The coefficient of determination indicates that 81.9% of the work effectiveness of employees at the Solok City Human Resources Development and Personnel Agency (BKPSDM) is affected by communication and the work environment, while the remaining 18.1% is influenced by other variables not addressed in this study.